Norbixin Protects Retinal Pigmented Epithelium Cells and Photoreceptors against A2E-Mediated Phototoxicity In Vitro and In Vivo - Fontaine, Valérie (PLoS One, 2016)
The accumulation of N-retinylidene-N-retinylethanolamine (A2E, a toxic by-product of the visual pigment cycle) in the retinal pigment epithelium (RPE) is a major cause of visual impairment in the elderly. Photooxidation of A2E results in retinal pigment epithelium degeneration followed by that of associated photoreceptors. Present treatments rely on nutrient supplementation with antioxidants. 9’-cis-Norbixin (a natural diapocarotenoid, 97% purity) was prepared from Bixa orellana seeds. It was first evaluated in primary cultures of porcine retinal pigment epithelium cells challenged with A2E and illuminated with blue light, and it provided an improved photo-protection as compared with lutein or zeaxanthin. In Abca4(-/-) Rdh8(-/-) mice (a model of dry AMD), intravitreally-injected norbixin maintained the electroretinogram and protected photoreceptors against light damage. In a standard rat blue-light model of photodamage, norbixin was at least equally as active as phenyl-N-tert-butylnitrone, a free radical spin-trap. Chronic experiments performed with Abca4(-/-) Rdh8(-/-) mice treated orally for 3 months with norbixin showed a reduced A2E accumulation in the retina. Norbixin appears promising for developing an oral treatment of macular degeneration. A drug candidate (BIO201) with 9’-cis-norbixin as the active principle ingredient is under development, and its potential will be assessed in a forthcoming clinical trial.